Evaluation of the Modified Clays in the Treatment of Car-washing Wastewater - Gyu Kim, Cheol; Joon Lee, Hyung; Muk Kim, Young; Jiang, J.Q. (Asian Journal of Chemistry, 2013)
The modification and use of clays as a new type of agents for the treatment of car washing effluent were investigated. The raw clays were montmorillonites K10 and KSF and were modified by either polymeric Al or Fe species, or an Al/Fe mixing polymeric species, or the cationic polymer species. The performance of modified clays was compared with aluminium sulphate, ferric sulphate and polyaluminium chloride in terms of the removal of turbidity, suspended solids, total COD and the oil contents (extracted with n-Hexane). The results demonstrated that after being modified with polymeric Al/Fe species, two montmorillonite clays possess greater properties to remove the particles (as suspended solids), organic pollutants (as COD) and oils from car-washing wastewater.